Implementation of Fuzzy Logic to Control Soil Moisture Level in Arduino-Based Rice Fields - Keinanjung Ruswandi; Lutfi Aziz Febrika Ardy; Muhammad Rafid Habibi Tambunan; Mohammad Iqsan Syachranie; Stephen Nathaniel; Wafi Hawali; Inna Novianty; Nanda Octavia; Ivan De NeroI (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
In Indonesia, where the agricultural sector is pivotal in the economy and most of the population are farmers, effective soil moisture control is crucial for optimizing crop production. This study investigates the application of modern technology, particularly Arduino microcontrollers utilizing Fuzzy Logic, to enhance irrigation management in rice fields. Given the challenges of irregular water supply due to geographical and temporal variations, additional infrastructure such as waterways, dams, and pumps are indispensable for regulating water distribution. By integrating Arduino microcontroller technology with Fuzzy Logic, precise and adaptive soil moisture management can be achieved, ensuring optimal water usage and improving crop yields. This research contributes to advancing sustainable agriculture in Indonesia, addressing the pressing need for food security amidst a growing population.